Islamic banks' brand personality and customer satisfaction: an empirical investigation through SEM. Issue 4 (3rd June 2021) - Jan, Muhammad Tahir; Shafiq, Ali
Abstract : Purpose: Brand personality plays an important role in affecting customer satisfaction. The Muslim population is estimated to reach 30% of the world's population, and it is considered as the fastest-growing religion in the world. To tap into this market, it is important to explore various aspects of business, in general, and marketing, in particular, from the perspective of Muslim consumers. The present research also attempts to do the same by proposing a conceptual model related to the brand personality of Islamic Banks, named, Islamic Banks' Brand Personality (IBBP) and its impact on customer satisfaction. Design/methodology/approach: This paper analyses the causal relationship that exists between the variables related to Islamic brand personality and customer satisfaction. For this purpose, data was collected quantitatively from 337 customers of different Islamic banks, through a self-administered questionnaire. The data analysis was conducted using SPSS and AMOS software. Factor analysis was performed to extract and decide on the number of factors underlying the measured variables of interest. Structural equation modelling was then used to examine the variables and the fitness of the proposed model. Findings: The result revealed that five out of the total six hypotheses were supported. In this case, trustworthiness and Shariah compliance resulted in the strongest impact on customer satisfaction followed by sincerity and justice. Practical implications: The positive significant impact of trustworthiness and Shariah compliance on customer satisfaction attests to the importance of these variables in the development of a strong brand personality in the context of Islamic banks. Policymakers of the financial industry in general and the Islamic financial service industry, in particular, may benefit from the findings of this study. Originality/value: There is a dearth of research conducted on investigating the impact of brand personality-related variables on the Islamic banking sector. The present research did not only develop variables of IBBP but also empirically tested their effect on customer satisfaction. This paper, therefore, offers invaluable insight into IBBP with its impact on customer satisfaction.